2015
DOI: 10.1007/s10803-015-2487-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Grammar Spared in Autism Spectrum Disorder? Data from Judgments of Verb Argument Structure Overgeneralization Errors

Abstract: Children with Autism Spectrum Disorder (ASD) aged 11-13 (N = 16) and an IQ-matched typically developing (TD) group aged 7-12 (N = 16) completed a graded grammaticality judgment task, as well as a standardized test of cognitive function. In a departure from previous studies, the judgment task involved verb argument structure overgeneralization errors (e.g., *Lisa fell the cup off the shelf) of the type sometimes observed amongst typically developing children, as well as grammatical control sentences with the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Several studies have suggested that children with ASD exhibit syntactic delays in comparison to peers with intellectual disability or TD. [34][35][36][37] These syntactic abnormalities can include challenges with verb phrases, regular and irregular past tense, present tense, and regular third person singular verbs. 35,36 However, like deficits in semantics, challenges in this domain of language are not universal among individuals with ASD; several studies have reported intact syntactic skills in individuals with ASD when compared with TD peers.…”
Section: Language Overview In Autism Spectrum Disordermentioning
confidence: 99%
“…Several studies have suggested that children with ASD exhibit syntactic delays in comparison to peers with intellectual disability or TD. [34][35][36][37] These syntactic abnormalities can include challenges with verb phrases, regular and irregular past tense, present tense, and regular third person singular verbs. 35,36 However, like deficits in semantics, challenges in this domain of language are not universal among individuals with ASD; several studies have reported intact syntactic skills in individuals with ASD when compared with TD peers.…”
Section: Language Overview In Autism Spectrum Disordermentioning
confidence: 99%
“…Performance on grammatical judgment of incorrect/correct sentences has shown children with ASD to be less sensitive than controls. 2 , 26 In some of the more recent research on this matter, there seems to be agreement that development of grammar generally may be delayed in children with ASD. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Future research, therefore, should attempt to extend the present findings to a more representative sample, by using experimental paradigms that place reduced task demands on children with ASD, or even play to their strengths (as Bennetto, 2009, andAmbridge, Bannard &Jackson, 2015, argue for grammaticality judgment tasks). One particularly promising paradigm is eye tracking (e.g., Brock, Norbury, Einav & Nation, 2008;Norbury, Brock, Cragg, Einav, Griffiths & Nation, 2009;Hahn, Snedeker & Rabagliati, unpublished observations), in which children are not required to make any responses at all, or indeed to do anything other than pay attention to visual and linguistic stimuli.…”
Section: Discussionmentioning
confidence: 98%